Flexural behavior of concrete-filled SHS and RHS aluminum alloy tubes strengthened with CFRP. (15th April 2020) - Zhu, Yao; Chen, Yu; He, Kang; Feng, Ran; Zhang, Xiaoyong; Zhu, Qingxia; Tang, Chao
Abstract: Conventional concrete-filled aluminum alloy tube (CFAT) can effectively delay the inward local buckling of aluminum alloy tube (AA). This paper experimentally and numerically investigates the suitability of strengthening square and rectangular hollow section (SHS and RHS) CFAT beams with a layer of carbon-fiber reinforcement polymer (CFRP) under four-point bending. Among 40 beams, 30 square and rectangular CFAT beams were strengthened with CFRP comprising three arrangement schemes of CFRP and 10 conventional square and rectangular CFAT beams were treated as reference beams. Flexural stiffness of square and rectangular CFAT beams are remarkably enhanced by external bonded CFRP, while the ductility is decreased. The bottom flange-bonded CFRP scheme is less effective in enhancing ultimate strength of CFAT beams than that of four sides-bonded CFRP scheme. New design approaches for evaluating both initial and post-yield flexural stiffness of square and rectangular CFAT beams strengthened with CFRP are proposed. FE models are correctly simulated to analyze the flexural behavior of square and rectangular CFAT beams strengthened with CFRP. CFRP strengthening technique using in this study can remarkably enhance the ultimate strength of square and rectangular CFAT beams and effectively delay the outward local buckling of AA tubes.